2020
DOI: 10.1111/hex.13032
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing researcher capacity to engage youth in research: Researchers’ engagement experiences, barriers and capacity development priorities

Abstract: BackgroundThere is increasing emphasis on engaging youth in research about youth, their needs, experiences and preferences, notably in health services research. By engaging youth as full partners, research becomes more feasible and relevant, and the validity and richness of findings are enhanced. Consequently, researchers need guidance in engaging youth effectively. This study examines the experiences, needs and knowledge gaps of researchers.MethodsEighty‐four researchers interested in youth engagement trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…Barriers and capacity development needs expressed prior to the workshop are presented in a companion manuscript. 26 That paper shows that while interest in and attitudes towards youth-engaged research were strong, skill development and practical training opportunities were found to be an important capacity development need.…”
Section: Backg Rou N Dmentioning
confidence: 96%
“…Barriers and capacity development needs expressed prior to the workshop are presented in a companion manuscript. 26 That paper shows that while interest in and attitudes towards youth-engaged research were strong, skill development and practical training opportunities were found to be an important capacity development need.…”
Section: Backg Rou N Dmentioning
confidence: 96%
“…Several studies have outlined potential barriers to youth engagement, such as limited practical resources and funding 40,41 . Despite the value of engagement, participants also highlighted barriers, such as time and funding constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement is increasingly valued by research organizations, such as the Strategy for Patient‐Oriented Research at the Canadian Institute for Health Research in Canada 45 and the Patient‐Centered Outcome Research Institute in the United States 46 . It is important to increase researchers’ capacity for youth and family engagement, through capacity development initiatives such as the INNOVATE Research project 18,40 . However, future work is needed to enhance and scale youth and family engagement practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A participatory evaluation workshop will be implemented to identify research questions and methods of interest and will present principles of evaluation and participatory research and a discussion to reflect on major issues of interest related to the intervention. Congruent with participatory approaches, the research team has successfully collaborated with youth in the past to co-create research questions and methods [26,30,60,61]. Research questions have often focused on current issues affecting youth.…”
Section: Participatory Youth Evaluationmentioning
confidence: 99%